2017
DOI: 10.1097/j.pain.0000000000000840
|View full text |Cite
|
Sign up to set email alerts
|

Observer influences on pain: an experimental series examining same-sex and opposite-sex friends, strangers, and romantic partners

Abstract: Despite the well-documented sex and gender differences, little is known about the relative impact of male-female social interactions on pain. Three experiments were conducted to investigate whether the type of interpersonal relationship men and women have with an observer affects how they respond to experimental pain. Study 1 recruited friends and strangers, study 2 examined the effects of same- and opposite-sex friends, whereas study 3 investigated the differences between opposite-sex friends and opposite-sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 46 publications
2
33
2
Order By: Relevance
“…This is particularly relevant, as observer and patient characteristics are known to influence pain decoding. 19 , 25 Researchers may also evaluate the influence of additional contextual features, such as observers' ethnicity and sex. 3 , 69 There would also be value in using manipulation checks in future research to ensure that experimental primes are perceived as intended.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant, as observer and patient characteristics are known to influence pain decoding. 19 , 25 Researchers may also evaluate the influence of additional contextual features, such as observers' ethnicity and sex. 3 , 69 There would also be value in using manipulation checks in future research to ensure that experimental primes are perceived as intended.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that romantic partners are more intimate and more willing to express their feelings than friends, whereas friends may not want to disclose pain during the task. 5 Thus, the empathetic expression of pain from a romantic partner rather than a friend might increase the pain intensity rating. Similarly, Chambers et al observed that, in mother-daughter dyads, the girls’ intensity ratings for cold pressor pain increased when their mothers interacted with them in an empathetic way.…”
Section: Discussionmentioning
confidence: 99%
“… 4 However, little is known about how perceived empathy influences pain in different social relationships. 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations